2015
DOI: 10.1002/jms.3600
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing ion mobility and collision cross section of fatty acids using electrospray ion mobility mass spectrometry

Abstract: This study investigated the ion mobility (IM) and the collision cross section (CCS) of fatty acids (FAs) using electrospray IM MS. The IM analysis of 18 FA ions showed intriguing differences among the saturated FAs, monounsaturated FAs, multi-unsaturated FAs, and cis-isomer/trans-isomer with respect to the aliphatic tail chains. The length of aliphatic tail chain present in the ion structures had a strong influence on the differentiation of drift, while the number of double bond showed a weaker influence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Additionally, IM-MS offers great potential in rapid separation of isomers that cannot be resolved with mass spectrometry alone. First demonstrated for structural isomers of polycyclic aromatic hydrocarbons [15], this potential has been shown across numerous classes of biological molecules including carbohydrates [1624], peptides [25, 26], oligonucleotides [19], lipids [19, 2729], amino acids [2931], fatty acids [32], glycans and glycopeptides [33], and other small molecules [34]. However, diastereomers and especially epimers, which differ in stereochemistry at a single chiral center, have very subtle structural differences that may contribute to only minor variation in CCS.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, IM-MS offers great potential in rapid separation of isomers that cannot be resolved with mass spectrometry alone. First demonstrated for structural isomers of polycyclic aromatic hydrocarbons [15], this potential has been shown across numerous classes of biological molecules including carbohydrates [1624], peptides [25, 26], oligonucleotides [19], lipids [19, 2729], amino acids [2931], fatty acids [32], glycans and glycopeptides [33], and other small molecules [34]. However, diastereomers and especially epimers, which differ in stereochemistry at a single chiral center, have very subtle structural differences that may contribute to only minor variation in CCS.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 When using IM-MS, isomer species of intermediates with the same m/z can be resolved quickly and efficiently due to different drift time ( Figure 1). [25][26][27][28][29][30][31][32][33][34] Furthermore, the collision cross-section (CCS) value closely related to the size of ions could be measured based on drift time. By comparing with the theoretical CCS value, the structure identification would be more accurate.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the experimental CCSs of leucine's protomers were measured referring to a reported method. [22] The computational process was done using a CCS calculator supported by Agilent IM Browsing software. Meanwhile, the theoretical CCSs were calculated based on the density functional theory.…”
Section: Characterization Of the Protomersmentioning
confidence: 99%
“…[12][13][14][15] Moreover, the collision cross section (CCS) can be calculated from IM, which is the size parameter related to the averaged momentum transfer impact area of a molecule. [16,17] It acquires many reliable results in the structural chemistry study [18][19][20][21][22] and intermediate study. [23] When a molecule is ionized in an MS ion source, protomers caused by the multi-protonation sites are often discovered.…”
Section: Introductionmentioning
confidence: 97%